The Comparison and Correlation of Serum Levels of Insulin and Na+/ K+ Atpase In Type 2 Diabetes Mellitus (T2DM) And Non-Diabetes Mellitus Individuals - Karar Kazem Mohammed; Ahmed Ghazi Sabbar; Haider Hafid Hmeash (Journal of Techniques, 2022)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic condition characterized by hyperglycemia that persists. Diabetes mellitus can cause damage to multiple organ systems, leading to the development of severe and life-threatening health issues, due to decreased insulin secretion, resistance to peripheral insulin effects, or both.